Glycoproteomic Sample Processing, LC‐MS, and Data Analysis Using GlycReSoft. Issue 3 (24th March 2021) - Wang, Meizhe; Shajahan, Asif; Pepi, Lauren E.; Azadi, Parastoo; Zaia, Joseph
Abstract: Identification of N ‐ and O ‐glycosylation on specific sites of proteins, along with glycan structural information, is necessary to determine the roles glycoproteins play in normal and pathologic cellular functions. Because such glycosylation is macro‐ and micro‐heterogeneous and alters the dissociation behavior of glycopeptides, specific sample preparation, mass spectrometry, and data analysis techniques are required. Advanced tandem mass spectrometry–based glycoproteomics coupled with powerful data mining algorithms are key elements for characterization of protein glycosylation. This article includes the detailed, streamlined sample preparation method for liquid chromatography–mass spectrometry data acquisition and subsequent bioinformatics‐based data annotation using the publicly available GlycReSoft program for highly efficient identification and quantification of glycoprotein glycosylation. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Characterization of glycans and site occupancy on purified glycoprotein Support Protocol 1 : In‐gel digestion of glycoproteins Support Protocol 2 : Detection of glycoproteins from cells/tissue through glycopeptide enrichment Basic Protocol 2 : Acquisition of glycopeptides through high‐resolution nano‐LC‐MS/MS Basic Protocol 3 : Identification and quantification of glycopeptides using GlycReSoft